Estimation of genetic diversity and relationship in sugar beet pollinators based on SSR markers - Ksenija Taški-Ajduković (Electronic Journal of Biotechnology, 2017)
Background: Genetic diversity studies are important for the selection of parents with a greater combination capacity that, when crossed, increase the chances of obtaining superior genotypes. Thus, 26 polymorphic simple sequence repeat (SSR) primers were used to assess the genetic diversity of 140 individual samples from 12 diploid sugar beet pollinators (pollen parents) and two cytoplasmic male sterile (cms) lines (seed parents). Eight pollinators originated from three research centers in the United States Department of Agriculture, while four pollinators and cms lines were from the Institute of Field and Vegetable Crops, Novi Sad, Serbia. Results: In total, 129 alleles were obtained, with a mean of 3.2 alleles per SSR marker. The observed heterozygosity ranged from 0.00 to 0.87 (mean = 0.30). Expected heterozygosity and Shannon's information index were the lowest for marker BQ590934 and the highest for markers SB15s and FDSB502s; the same markers were the most informative, with PIC values of 0.70 and 0.69, respectively. Three private alleles were found in pollinator EL0204; two in pollinator C51; and one in pollinators NS1, FC221, and C93035. Molecular variance showed that 77.34% of the total genetic variation was attributed to intrapopulation variability. Cluster and correspondence analysis grouped sugar beet pollinators according to the breeding centers, with few exceptions, which indicate that certain amount of germplasm was shared, although centers had their own breeding programs. Conclusions: The results indicate that this approach can improve the selection of pollinators as suitable parental components and could further be applied in sugar beet breeding programs.